Analisis Data Satelit Altimetri Dalam Pemantauan Gelombang Laut di Perairan Provinsi Bengkulu - Yarmanto, Risky Budi; Irkhos, Irkhos; Suhendra, Suhendra; Lizalidiawati, Lizalidiawati (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2025)
Bengkulu Province, located on the west coast of Sumatra Island and facing directly onto the Indian Ocean, causes sea waves in Bengkulu Waters to be directly influenced by its geographical conditions. Sea waves in Bengkulu Waters vary due to the influence of monsoon winds and global climate. Seasonal variations in significant wave height (SWH) obtained from altimetry satellite imagery in five regions representing Bengkulu, namely Mukomuko Waters, North Bengkulu, Bengkulu City, Seluma, and Kaur can be used to monitor sea waves. The coordinates of the five regions representing Bengkulu Waters are as follows: Mukomuko is located at 2°40'20.82